Chlamydomonas reinhardtii-derived multimer Mytichitin-CB possesses potent antibacterial properties. (September 2020) - Hadiatullah, Hadiatullah; Wang, Hui; Liu, Yan-Xia; Fan, Zhen-Chuan
Graphical abstract: Highlights: Mytichitin-CB was stably expressed in Chlamydomonas reinhardtii . C. reinhardtii -derived Mytichitin-CB displayed a broad antibacterial spectrum. C. reinhardtii -derived Mytichitin-CB resisted temperature, pH and proteases. C. reinhardtii -derived Mytichitin-CB was non-toxic to mammalian and human cells. C. reinhardtii -derived Mytichitin-CB disrupted membrane integrity of bacteria. Abstract: Mytichitin-CB was isolated from Mytilus coruscus in 2014. This antimicrobial peptide shows a weak inhibitory effect on Gram-negative bacteria but inhibits the growth of Gram-positive bacteria and fungi efficiently. Here, a C-terminal hemagglutinin and 6×Histidine (HA-6×His) double tagged three tandem repeats of Mytichitin-CB (3×Mytichitin-CB) with a molecular weight of about 21.5 kDa was expressed in Chlamydomonas reinhardtii . The recombinant 3×Mytichitin-CB was stably expressed following continuous sixth passages of cells and inhibited the growth of both Gram-negative and Gram-positive bacteria at maximum inhibitory concentration (MIC) values between 30 and 50 μg/mL. 3×Mytichitin-CB was stable in terms of its antibacterial activity when treated by a wide range of temperatures and pHs and was resistant to digestion by various proteases. C. reinhardtii -derived 3×Mytichitin-CB had low hemolytic activity and cell cytotoxicity. Moreover, 3×Mytichitin-CB efficiently caused changes on the cell morphology by destroying membrane integrity of the tested bacteria. Our data thus, for the first time, show that C. reinhardtii is a suitable host for stably expressing recombinant 3×Mytichitin-CB, which possesses potent antibacterial properties.